Analisis Perbandingan Penerapan Sukuk Mudharabah dalam Sistem Keuangan Syariah Indonesia dan Qatar - Maulida Rahma; Tri Wina Sabrina; Dian Zahra Syahfitri Lubis; Maryam Batubara (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the implementation of the mudharabah sukuk contract in Indonesia and Qatar as a Sharia-compliant financing instrument based on partnership principles. Mudharabah is a form of cooperation between the capital provider (shahibul maal) and the entrepreneur (mudharib), in which profits are shared according to a pre-agreed ratio and without any guarantee of fixed returns. This research uses a qualitative descriptive method with a literature review approach, examining academic sources, fatwas from the Indonesian Ulema Council (DSN-MUI), and practical applications in Islamic financial institutions in both countries. The findings reveal that in Indonesia, mudharabah sukuk is legally recognized through DSN-MUI Fatwa No. 41/DSN-MUI/IV/2004 and has been implemented in the form of corporate sukuk. However, its development remains limited due to market preference for fixed-return instruments like ijarah sukuk, low Sharia financial literacy, and the unpreparedness of project structures. In contrast, in Qatar, mudharabah sukuk has evolved more significantly with strong support from established Islamic financial institutions such as Qatar Finance House, active involvement of internal Sharia supervisory boards, and a high level of business transparency, making the structure more compliant with Islamic principles and attractive to risk-conscious investors. These findings highlight the importance of strengthening regulatory oversight and market education to ensure that mudharabah contracts can be applied optimally and in full accordance with their intended values of justice and risk-sharing.